Cochrane corner: is integrated disease management for patients with COPD effective?. Issue 11 (9th January 2014) - Kruis, Annemarije L; Smidt, Nynke; Assendelft, Willem J J; Gussekloo, Jacobijn; Boland, Melinde R S; Rutten-van Mölken, Maureen; Chavannes, Niels H
Abstract : Patients with COPD experience respiratory symptoms, impairments of daily living and recurrent exacerbations. The aim of integrated disease management (IDM) is to establish a programme of different components of care (ie, self-management, exercise, nutrition) in which several healthcare providers (ie, nurses, general practitioners, physiotherapists, pulmonologists) collaborate to provide efficient and good quality of care. The aim of this Cochrane systematic review was to evaluate the effectiveness of IDM on quality of life, exercise tolerance and exacerbation related outcomes. Searches for all available evidence were carried out in various databases. Included randomised controlled trials (RCTs) consisted of interventions with multidisciplinary (≥2 healthcare providers) and multitreatment (≥2 components) IDM interventions with duration of at least 3 months. Two reviewers independently searched, assessed and extracted data of all RCTs. A total of 26 RCTs were included, involving 2997 patients from 11 different countries with a follow-up varying from 3 to 24 months. In all 68% of the patients were men, with a mean age of 68 years and a mean forced expiratory volume in 1 s (FEV1 ) predicted value of 44.3%. Patients treated with an IDM programme improved significantly on quality of life scores and reported a clinically relevant improvement of 44 m on 6 min walking distance, compared to controls. Furthermore, the number of patients with ≥1 respiratory related hospital admission reduced from 27 to 20 per 100 patients. Duration of hospitalisation decreased significantly by nearly 4 days.